Influences of customary and statutory governance on sustainable use and livelihoods: The case of baobab, Chimanimani District, Zimbabwe - Kozanayi, Witness (Department of Environmental and Geographical Science, 2019)
Scholars have engaged actively with the link between customary practices and ecological conservation in Africa as part of a broader debate on governance approaches for natural resource management. To a large extent, this is in response to a growing voice articulating the need to integrate traditional institutions and customary practices into a more contemporary form of governance for Africa’s democratic and socio-economic transformation. To date, however, the integration of customary and statutory approaches to governance has yielded only modest progress in the forest sector and knowledge remains limited about the interface between these governance systems and the effect of this dualism on natural resource management. Using the lens of the baobab tree, this research set out to address these gaps and to elucidate understanding of the interplay between customary and statutory governance in managing natural resources; the influence of such interactions on ecological sustainability and livelihoods; and the contextual factors that shape such approaches. Uses of the baobab tree as well as factors affecting access were analysed. Two study sites were selected on the basis of similarities in resource endowment and contrasting use patterns and forms of governance. Both quantitative and qualitative methods were used. Quantitative methods included an ecological survey to examine the relationship between different indicators of ecological sustainability and different tenure regimes. A household survey was also carried out to examine the extent to which households use and benefit from baobab products. Qualitative methods included focus group discussions, institutional mapping, ranking and scoring, and oral histories. The study engaged with debates around governance, bricolage, non-timber forest products, bifurcation, livelihoods and access. Findings show that the baobab tree is used in multiple ways by households, and has both consumptive values as well as intrinsic values which are typically overlooked in the discourse of natural resource governance. The study illustrates that the interest of traditional institutions in regulating baobab use and access has been informed by reasons relating to sustainable livelihoods, ecological sustainability and the need to maintain a delicate link between environmental sustainability, the spirits of the land and resource users. Local arrangements are robust, dynamic and are entrenched in the day to day lives of the resource users. These arrangements may not fit into existing technical toolkits or environmental blueprints, and policy from the top may not be connecting with reality on the ground. Although traditional authorities and customary practices have remained relevant for local people in the realm of resource governance, they are weakening in the face of commercial baobab use. Where statutory forms of governance are overlaid onto existing customary forms of governance without due regard for local practices, unintended consequences arise. A key finding is that history profoundly informs the way local people harvest and use resources due to the long trajectory of the interplay between customary and statutory forms of governance that spans back to the colonial era. The main conclusion from the study is that both customary and statutory systems of governance are important, but need to be used in a graduated manner. Statutory forms of governance can be introduced to assist customary practices on a demand-driven basis. Results emphasise the importance of considering seemingly peripheral forms of governance such as customary practices within the continuum of resource governance in rural areas.